Why People with Overweight and Obesity Are Seeking Care Through Digital Obesity Services: A Qualitative Analysis of Patients from Australia’s Largest Digital Obesity Provider - Louis Talay; Matt Vickers; Sarah Loftus (Telemedicine Reports)
Background: Increasingly large numbers of people with overweight and obesity (PWOO) are seeking care through digital services. Digital weight-loss service (DWLS) advocates claim that this is due to the modality’s mitigation of obesity care access barriers. However, influential health bodies have consistently argued that DWLSs are solely focused on facilitating access to weight-loss medications—an approach that compromises patient safety. Although modern weight-loss medications have demonstrated unprecedented effectiveness in clinical trials, they should only be prescribed under strict safety guidelines and used as a supplement to lifestyle therapy. Major health institutions have also stressed the importance of continuous multidisciplinary care in the treatment of overweight and obesity. Despite the surging global uptake of DWLSs, scholars are yet to investigate whether such services increase access to quality obesity care or are simply businesses offering an easier pathway to weight-loss medications. A vital preliminary step in addressing this complex question is to understand patient motivations for using DWLSs rather than face-to-face alternatives. The study aimed to qualitatively assess the reasons PWOO subscribe to Australia’s largest DWLS. Methods: The study applied a purposive sampling strategy, limiting recruitment to patients who had been approved by a doctor for the Eucalyptus DWLS and paid their first monthly subscription but were yet to receive their first GLP-1 RA order and commence treatment. Recruitment ceased once thematic saturation was attained across a comparable number of male and female patients. All phone interviews were scheduled according to patient preferences and took place between April 8 and May 7, 2024. Transcripts from interviews were thematically analyzed using the Braun and Clarke method to establish reasons for subscription to the Eucalyptus DWLS. Results: In total, 4962 patients satisfied the recruitment criteria of whom 197 participated in phone interviews. Most participants were of Caucasian heritage (61%), and the mean age and body mass index were 40.4 (±10.4) years and 34.4 kg/m2 (±5.6), respectively. From our analysis, five key themes emerged in relation to the reasons PWOO chose to treat their condition with the Eucalyptus DWLS: failure to achieve weight-loss goal through stand-alone lifestyle interventions, marketing and brand awareness, difficulty accessing comprehensive weight-loss care through local general practitioner, more comfortable receiving weight-loss therapy through digital platforms, and patients value the flexibility of asynchronous DWLS consults. Discussion: This study established an important foundation in digital obesity care literature, generating findings that support both sides of the DWLS utility debate. The identified themes should inform future quantitative analyses of patient DWLS motivations.